2021
DOI: 10.1111/tid.13623
|View full text |Cite
|
Sign up to set email alerts
|

Sources and prevention of graft infection during long‐term ex situ liver perfusion

Abstract: Introduction The use of normothermic liver machine perfusion to repair injured grafts ex situ is an emerging topic of clinical importance. However, a major concern is the possibility of microbial contamination in the absence of a fully functional immune system. Here, we report a standardized approach to maintain sterility during normothermic liver machine perfusion of porcine livers for one week. Methods Porcine livers (n = 42) were procured and perfused with blood at 34°C following aseptic technique and stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…However, during short-term (5 h) perfusion, the effect of infections is expected to be limited, and no pockets of infections were shown by histology. Nevertheless, to reach long-term perfusion, the addition of antibiotics is necessary [ 39 ], and future research should focus on the risk of bacterial infections due to slaughterhouse harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…However, during short-term (5 h) perfusion, the effect of infections is expected to be limited, and no pockets of infections were shown by histology. Nevertheless, to reach long-term perfusion, the addition of antibiotics is necessary [ 39 ], and future research should focus on the risk of bacterial infections due to slaughterhouse harvesting.…”
Section: Discussionmentioning
confidence: 99%
“…Eshmuminov et al also explored the best preventative strategy during 7-day NMP and found microbial contamination, mostly from an external source, probably due to operating the perfusion machine. They also showed that continuous infusion of piperacillin-tazobactam was preferred over a daily bolus to maintain a stable concentration (101).…”
Section: Sterile Environmentmentioning
confidence: 99%
“…The most common organisms seen during ECMO are coagulase-negative staphylococci, Candida spp., P. aeruginosa, S. aureus, Enterococcus, Enterobacter spp., and S. maltophilia, which are also common organisms for the majority of the non-ECMO device and procedure-related healthcare-associated infections and were also found during 7-day liver perfusions (101,104,105). Fungal infections are not often seen.…”
Section: Sterile Environmentmentioning
confidence: 99%
“…For these reasons, the use of antibiotics during NMP of the liver is well established and has been a part of each group’s clinical protocol. In the development phase of the study of Eshmuminov et al [ 106 ], microbial contamination occurred in 69% of porcine livers with a mean occurrence of growth on 4 ± 1.6 perfusion days. So, they switched the antimicrobial infusion in a continuous application, reduced the perfusate sampling and avoided taking liver biopsies; as a result, no more microbiological growth was observed perfusing the livers ex situ up to 1 week.…”
Section: Surgical Frontiers Of Ex Situ Liver Perfusionmentioning
confidence: 99%